Nurse Educator Certification: Overview and Evaluation of the Canadian Association of Schools of Nursing Program (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2022)
The Canadian Association of Schools of Nursing (CASN) has spearheaded an education institute and fostered the growth of an accessible cadre of innovative educational programming that were built on identified national nursing educator competencies. The purpose of this article is to outline the development and structure of the CASN Canadian Nurse Educator Certification Program, share an analysis of one aspect of program evaluation data and summarize the program’s current value to nurse educators. The program offers flexible professional development for Canadian nurse educators through three online modules that prepare participants to sit the national certification exam and attain the designation of Canadian Certified Nurse Educator (CCNE). Part of an ongoing program evaluation conducted by CASN in 2021 sought to provide information on the perception of certification of nurse educators in Canada. A review of the process of module delivery that prepares educators to sit the certification exam and how certification is perceived as valuable or not by nurse educators was the focus. The CCNE program participants’ perspectives on the value of module learnings in terms of academic practice were evaluated using the Perceived Value of Certification Tool for the Nurse Educator. Of the 108 respondents to the survey questions, the findings indicate that most CCNE nurse educators perceived that there is value in nurse educator certification. A key survey finding was that educators perceived intrinsic value more so than extrinsic value in obtaining certification. Overall, the respondents believed that certification was not fully recognized by employers, colleagues, or students and that enhancing others’ perceptions of certification was needed. Despite consistent enrolments in the CASN program modules, the program and CCNE designation appear to require further formal recognition from teaching and academic institutions across the country. With the shortage of qualified nursing faculty, the need to strengthen current academic faculty members’ competencies is imperative. The certification and credentialing of academic nurse educators needs to be recognized. Educators should be provided merit for the acquisition of the specialized knowledge, expertise, and competencies required for the role.